TRENDS AND PROSPECTS FOR THE DEVELOPMENT OF HIGHER EDUCATION IN UZBEKISTAN - Abduvasikov Abduaziz Abdulazizovich; Mynbaeva Aygul Utepbergen kizi (Western European Studies, 2024)
The higher education system in Uzbekistan is undergoing significant transformations aimed at meeting the demands of a rapidly changing economic landscape. This paper examines the current trends and emerging prospects for the development of higher education in Uzbekistan, focusing on the reform processes, challenges faced, and strategic initiatives aimed at enhancing educational quality. With the global shift towards a knowledgebased economy, Uzbekistan's educational policies are increasingly prioritizing innovation, international collaboration, and workforce readiness. The findings underscore the importance of aligning higher education with labor market needs and the critical role of technology in facilitating learning and research.
Keywords: Higher education; Uzbekistan; educational reform; qualification of the workforce